PENGARUH ETIKA PROFESI, INDEPENDENSI AUDITOR, DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT - Audri Tama Anggraini (2020)
This research is a quantitative study that aims to determine the effect of professional ethics, auditor independence, and work experience on audit quality. The sample used in this study was an auditor who worked at a public accounting firm in South Jakarta that was conducted randomly. The analysis technique used in this study is SPSS with a significance level of 5%. The results of this study were obtained as follows, that professional ethics had a significant effect on audit quality, while auditor independence and work experience had no significant effect on audit quality. Keywords: professional ethics, auditor independence, work experience, audit quality.